Wound Dressings for Hip and Knee Total Joint Arthroplasty: A Narrative Review. Issue 7 (July 2021) - Rothfusz, Christopher A.; Emara, Ahmed K.; McLaughlin, John P.; Molloy, Robert M.; Krebs, Viktor E.; Piuzzi, Nicolas S.
Abstract : Dressing choice following lower-extremity total joint arthroplasty has substantial ramifications for postoperative outcomes and should be carefully made to prevent complications such as periprosthetic joint infection. Patient risk factors are essential components in the selection of wound dressings in total joint arthroplasty. Traditional dressings are inexpensive per unit; nevertheless, the associated higher complication profile in patients at a high risk for poor wound healing and sequelae-associated costs may outweigh the up-front savings. Modern dressings have the potential to yield better safety outcomes and increased patient satisfaction; however, there is a paucity of evidence regarding the ideal interactive dressing. Active dressings, such as silver-ion dressings and closed-incisional negative-pressure wound therapy, have shown promising results to reduce surgical site and periprosthetic joint infection, especially in patients at a high risk for poor wound healing following hip and knee total joint arthroplasty.